Corporate claims against directors or officers following the company’s unlawful conduct - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2016)
When a company enters into a transaction or undertakes an action that turns out to be either illegal or otherwise exposes the company to substantial fines or other pecuniary sanctions, the question arises as to whether the company may then recover its fines, expenses and other losses from its directors and employees, in the absence of the relevant legislation specifically providing for, or denying a claim by, the company. In these cases, the board may have made a specific decision to cause the company to enter into the unlawful conduct or may have failed to prevent the improper conduct from undertaken by its employees or officers acting on the company’s behalf. This paper assumes that the directors or employees have not acted dishonestly or otherwise breach the no-conflict or no-profit rule. While the board is not likely to sue one of its own members, the action may be brought by a differently constituted board or shareholders pursuant to the statutory derivative action.